Bioactivity and Characterization of Karaya Gum (Journal of Pharmaceutical Negative Results, 2022)
Natural Biopolymers has much applications and do possess various bioactivity. In this study, karaya gum was collected and used for bioactivity studies. Gum was subjected for phytochemical screening and characterized using thin layer chromatography (TLC), UV-Vis Spectrophotometer, FTIR. It was also subjected for bioactivity studies like antibacterial against E.coli and S.aureus and antioxidant activity. Karaya gum showed a good antioxidant and antibacterial activity against E.coli and S.aureus. UV-VIS spectroscopy analysis showed the presence of sugars like sucrose, glucose, xylose etc. FTIR analysis showed the presence of functional groups like alcohol, phenols, aldehydes, ketones.